Profil Lipid Pada Masyarakat Peminum Kopi di Babadan Dusun Plumbon Kelurahan Banguntapan Bantul - Barinta Widaryanti; Nasa Hamidatussalamah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Coffee is the most widely consumed in the world, although the health impact of coffee drinking remains controversial. The objective of this study was to determine the lipid profile of traditional coffee drinker. The subject of this research were 30 residents of Babadan village, Plumbon hamlet, aged range 20-65 years old, who had a traditional coffee drinking habituation. Lipid profile data were obtained by measuring serum levels of total cholesterol, LDL, HDL and triglyceride using enzymatic photometric method. Descriptive analysis was conducted by examining the characteristics of the subjects, including age, gender and average levels of total cholesterol, LDL, HDL and triglyceride. The correlation between the amount and duration of coffee consumption on lipid profiles was analiyzed using simple regression analysis. The result showed that 6-% of the subject were male  and 40% were female. Most subjects were within 19-44 age range. There were no differences in total cholesterol, LDL and triglyceride levels between male and female, but HDL levels were higher in females. The correlation between the duration of coffee consumption and lipid profile showed a very weak relationship, with R value of 0-0.25. similarly, the amount of coffee consumed was also very weakly correlated with lipid profile, with R value of 0-0.25. the conclution of this study was that neither the duration nor the amount of coffee consumption effects the lipid profiles of traditional coffee  drinker in Babadan village, Plumbon Hamlet.